2023
DOI: 10.3390/ijerph20032294
|View full text |Cite
|
Sign up to set email alerts
|

Early Origins of Chronic Obstructive Pulmonary Disease: Prenatal and Early Life Risk Factors

Abstract: The main risk factor for chronic obstructive pulmonary disease (COPD) is active smoking. However, a considerable amount of people with COPD never smoked, and increasing evidence suggests that adult lung disease can have its origins in prenatal and early life. This article reviews some of the factors that can potentially affect lung development and lung function trajectories throughout the lifespan from genetics and prematurity to respiratory tract infections and childhood asthma. Maternal smoking and air pollu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
6
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 23 publications
(17 citation statements)
references
References 195 publications
0
6
0
Order By: Relevance
“…obstructive lung disease in adulthood [5]. Recent studies have confirmed older investigations in describing the independent risk of dysanapsis in COPD [6].…”
Section: Computed Tomography Scans and Chronic Obstructive Pulmonary ...mentioning
confidence: 62%
See 1 more Smart Citation
“…obstructive lung disease in adulthood [5]. Recent studies have confirmed older investigations in describing the independent risk of dysanapsis in COPD [6].…”
Section: Computed Tomography Scans and Chronic Obstructive Pulmonary ...mentioning
confidence: 62%
“…Dysanapsis is believed to arise early in life [4]. A more recent study suggests that determination of lung morphology occurs at a young age and that genetic factors, prenatal, perinatal, and childhood lung development may be critical in the development of obstructive lung disease in adulthood [5]. Recent studies have confirmed older investigations in describing the independent risk of dysanapsis in COPD [6].…”
Section: Computed Tomography Scans and Chronic Obstructive Pulmonary ...mentioning
confidence: 87%
“…Alterations in lung function during childhood have been found to predict adult lung function and the onset of clinical pathology, including the development of chronic obstructive pulmonary disease (COPD). The fact that premature patients, particularly those with BPD, exhibit initial lung function abnormalities makes them particularly vulnerable to the early onset of respiratory failure in adulthood [32,33]. Recent studies have indicated a higher incidence of COPD among individuals born at younger gestational ages [1], especially among those diagnosed with BPD [33].…”
Section: Discussionmentioning
confidence: 99%
“…This widespread habit could impair the intrauterine environment and adversely affect the developing organs of offspring. 3 , 4 Previous studies have extensively documented the correlation between maternal smoking during pregnancy and low birth weight, 5 , 6 , 7 premature births, 8 congenital heart defects, 9 , 10 chronic obstructive pulmonary disease, 11 anxiety and depression, 12 and other disorders in offspring.…”
Section: Introductionmentioning
confidence: 99%